Tugas Guru Menurut Syed Muhammad Naquib Al-Attas dan Aktualisasinya dalam Pendidikan Islam - Muhammad Hamsah; Nurchamidah Nurchamidah (Tafhim Al-'Ilmi, 2022)
Abstract Muhammad Naquib al-Attas argued that the primary thing in education is the process. Yet, three basic elements (core inherent) in education; humans and their fitrah concept, educational content, and attitude also become other important things to be considered. Thus, a teacher has several duties as follow; first, comprehending humans and their fitrah, means that they are assumed as learners who have great potential since birth. Second, understanding the aim of education. The ultimate duties of a teacher as able to comprehend and convey the core of the education well. Third, conveying good attitude. In case, attitude, appearance and other are highlighted and copied by them. In sum, those duties will make Islamic education be renewal of this time as the initiate of Islamic concept in science and moral concepts in education. Â  Keywords: Teacherâ€™s job, Islamic Studies, Naquib Al-Attas